Management of Abdominal Hernias (Springer International Publishing, 2018)
The fifth edition of this well-received book contains all the latest information on surgical techniques in abdominal hernia surgery and has been updated to reflect progress in robotic hernia surgery and minimally invasive approaches, as well as new materials used such as fully resorbable synthetic meshes. With chapters on management of complications and laparoscopic repair, among others, the book also contains newly-added accounts of the Milos technique, laparoscopic primary closure of defects and mesh. For each of the surgical techniques described the reader will find information on pre- and post-operative management, instructions on theatre set-up and patient positioning, an account of the incision and access, as well as detailed operative steps and closure, and finally tips and pitfalls. From financial aspects to operative techniques and materials, this book provides a very comprehensive account of abdominal hernia management. Richly illustrated to demonstrate the surgical procedures in detail this book is written by a team of world leaders in herniology. This is an indispensable guide to herniologists and hernia surgeons, worldwide.